STUDI KOORDINASI PERALATAN PROTEKSI OCR DAN GFR PADA PENYULANG TIBUBENENG - Baskara, Indra; Sukerayasa, I W.; Ariastina, W. G. (Majalah Ilmiah Teknologi Elektro, 2015)
Tibubeneng feeder equipped with protective devices over current relay (OCR) and ground fault relay (GFR) installed in Recloser Dama, Recloser Tandeg and relay feeder Tibubeneng in GI. Based on data from PLN Bali, there are 3 times the interference with the feeder Tibubeneng that cause coordination protection error system. The problem of protection error coordination can be addressed by the study coordinated analysis of protection systems. The analysis was performed by making a curve existing coordination OCR settings and GFR in Tibubeneng feeders and comparing it with the coordination curve setting calculation results. The calculation is performed based on the standards system of protection of sensitive, reliable, fast and remain selective. Based on the analysis of the existing curve setting, an error occurred coordination between the curve and the GFR Recloser Recloser Tandeg Dama indicated by the curves that intersect at several levels of short circuit current value and the value of grading time OCR and GFR was less than 0.4 seconds. Repair work coordination OCR and GFR in Tibubeneng feeder can be done by re-setting in accordance with the results of calculations in order to obtain protection system in accordance with the terms of the security system
Keywords: Over Current Relay, Ground Fault Relay, Koordinasi Proteksi